Pengaruh Fungsi Keluarga, Dukungan Sosial, dan Beban Perawatan terhadap Ketahanan Keluarga yang tinggal bersama Lansia - Dewi, Siska Ayu Tiara; Herawati, Tin; Muflikhati, Istiqlaliyah (Institut Teknologi Sepuluh Nopember, 2024)
As Indonesia enters the era of an aging society, protecting the elderly becomes increasingly important, particularly for family members who serve as primary caregivers. This study aims to analyze the impact of family characteristics, elderly characteristics, family functions, social support, and caregiving burden on family resilience. The research sample consisted of families with elderly members in the household, focusing specifically on wives as respondents in the Kemang District, Bogor Regency. We collected data through direct interviews with 120 respondents and analyzed them using descriptive and inferential statistical methods. The findings reveal that family function and social support have a significant and positive impact on family resilience. These factors contribute to the family's ability to adapt, cope, and maintain stability despite the challenges of caring for elderly members. Conversely, the burden of caregiving has a significant negative impact on family resilience, indicating that higher caregiving demands can strain family resources and emotional well-being. This study underscores the importance of strengthening family functions and enhancing social support systems to bolster family resilience in the face of aging-related challenges. Addressing these factors can help to improve the quality of care for the elderly and support the well-being of families in Indonesia's aging society.